EFFECT OF FEED COMPOSITION ON SPONSTIC PLASTIC WASTE DEGRADATION, SURVIVALITY AND LARVA GROWTH Tenebrio molitor L. - Wachju Subchan; Lintang Mutiara Putri; Dwi Wahyuni; Sugeng Winarso (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2022)
Sponge plastic is one of the plastic wastes that is difficult to degrade. Recently research reported that Tenebrio molitor L larvae have the potential capability to degrade plastic waste. But still a lack information according to the effect of feed composition on survival, and growth of T. molitor L larvae. The purpose of this study was to determine the effect of plastic feed composition on the rate of degradation of sponge plastic waste, survival, and growth of T. molitor L larvae. The method used in this study was an experimental laboratory using Completely Randomized Design (CRD) and using controls and six treatments with 3 repetition times. The parameters measured in this study were survival (%), body length growth (cm/week) and body biomass (gram/week), and degradation rate (gram/week). The data obtained from the research results will be analyzed using ANOVA which is then tested by Duncan. The results showed that feed composition had a significant effect (p=0.001) on the rate of degradation of plastic sponge waste, survival (p=0.000), and growth (p=0.001) of T. molitor L larvae. degradation, survival, and growth of T. molitor L. larvae.